2018
DOI: 10.1039/c8ra07841f
|View full text |Cite
|
Sign up to set email alerts
|

Substrate switchable Suzuki–Miyaura coupling for benzyl ester vs. benzyl halide

Abstract: Two reaction conditions were developed to accomplish the substrate switchable (benzyl esters vs. benzyl halides) Suzuki–Miyaura coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Suzuki–Miyaura coupling reactions of benzyl derivatives were first reported in the 1990s and found to proceed in general less efficiently than the analogous coupling reactions with aryl halides . This has led to several modifications and improvements, including the use of potassium aryltrifluoroborates instead of arylboronic acids, more elaborate precatalysts and the development of special conditions for chemoselective cross-coupling at benzyl or aryl positions . Taylor and co-workers reported that the cross-coupling of 18 and 19 to diarylmethane 20 proceeds with a low amount of the succinimide (succ) ligated Pd-catalyst [ trans -PdBr­( N -succ)­(PPh 3 ) 2 ], using both coupling partners in equimolar ratios .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suzuki–Miyaura coupling reactions of benzyl derivatives were first reported in the 1990s and found to proceed in general less efficiently than the analogous coupling reactions with aryl halides . This has led to several modifications and improvements, including the use of potassium aryltrifluoroborates instead of arylboronic acids, more elaborate precatalysts and the development of special conditions for chemoselective cross-coupling at benzyl or aryl positions . Taylor and co-workers reported that the cross-coupling of 18 and 19 to diarylmethane 20 proceeds with a low amount of the succinimide (succ) ligated Pd-catalyst [ trans -PdBr­( N -succ)­(PPh 3 ) 2 ], using both coupling partners in equimolar ratios .…”
Section: Resultsmentioning
confidence: 99%
“…89 This has led to several modifications and improvements, including the use of potassium aryltrifluoroborates instead of arylboronic acids, 89 more elaborate precatalysts 90 and the development of special conditions for chemoselective cross-coupling at benzyl or aryl positions. 91 Taylor and co-workers reported that the crosscoupling of 18 and 19 to diarylmethane 20 proceeds with a low amount of the succinimide (succ) ligated Pd-catalyst [trans-PdBr(N-succ)(PPh 3 ) 2 ], using both coupling partners in equimolar ratios. 90 Unfortunately, commercial availability of this precatalyst is nowadays limited and its synthesis has, to the best of our knowledge, not been sufficiently documented.…”
Section: Scope Of Matsuda−heck Couplingmentioning
confidence: 99%
“…The diarylmethane framework, which is constructed using the Suzuki-Miyaura coupling reaction, is a crucial building block in the synthesis of therapeutic drugs, such as aryl-diketo acid [22], trimethoprim [23], and cinnamic acylsulfonamide (the human EP3 receptor L-798106) [24] (Figure 2), polymers [25][26][27], and dyes [3,28]. Benzyl halides are some of the most commonly used electrophilic partners for Pd-catalyzed coupling reactions [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The catalytic cross-coupling reaction for diarylmethane synthesis has several limitations, including high catalyst loading, long reaction times, and substrate scope.…”
Section: Suzuki Coupling Reaction Studies Of Benzyl Chlorides In Aque...mentioning
confidence: 99%
“…[19][20][21] Additionally, various organic light emitting devices have been fabricated using different donor-acceptor based organic scaffolds including 1,2,3-triarylbenzenes, 22,23 benzo[f]quinolines and benzo[a]acridines, 24 fluoranthenes, 25 fluorenes and fluorenones. 26 Various routes are available in the literature to achieve the synthesis of diarylmethanes but most of them are linked with transition metal-catalyzed cross-coupling reactions [27][28][29][30][31][32] and Friedal-Craft benzylation of arenes using benzylic alcohols/halides. 33,34 Recently, Singh and Kole developed a metal-free approach for the synthesis of functionalized diarylmethanes by the ring transformation of 2H-pyran-2-ones with 1,3-diphenylacetone under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%